2016
DOI: 10.15740/has/ijppht/7.1/151-156
|View full text |Cite
|
Sign up to set email alerts
|

Some studies on curing and drying characteristics of turmeric rhizomes

Abstract: Turmeric is an important commercial spice crop grown in India and it is named as "Indian saffron". Turmeric is grown in tropical countries like India,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It is an essential operation before drying to avoid the raw odor, destroy the vitality of fresh rhizomes, yield uniformly colored product, and reduce the drying time [6]. The method of curing turmeric varies from place to place [7]. There are conventional and improved methods of curing turmeric; however, during the conventional method of boiling turmeric, contents might be leached along with water, which in turn lowers curcumin, oleoresin and essential oil contents [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an essential operation before drying to avoid the raw odor, destroy the vitality of fresh rhizomes, yield uniformly colored product, and reduce the drying time [6]. The method of curing turmeric varies from place to place [7]. There are conventional and improved methods of curing turmeric; however, during the conventional method of boiling turmeric, contents might be leached along with water, which in turn lowers curcumin, oleoresin and essential oil contents [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods of drying that use different forms of heating; however, solar energy is important for drying agricultural products. Since other conventional sources of energy are in the declining trend in their availability, several researchers reported that solar energy is beneficial for drying agricultural products, particularly in the tropics where good sunshine is available during most of the year and (a) is pollution-free, (b) available at minimal cost, and (c) dries faster [7].…”
Section: Introductionmentioning
confidence: 99%